Bahasa Inggris - Chairunnisa, Mutiara Rizqa; Viruliana, Fajrina Margareth (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
Communication in the family is an important factor in determining the good or bad attitude of children. Parents play an important role in educating their children. In the Koran there are many communication between parents and children, one of which is communication between the prophet Abraham and his son, the prophet Ismail. The story of the prophet Ibrahim and the prophet Ismail is a good example for parents and children to be able to communicate well while still prioritizing the aspect of obedience to Allah SWT. This is stated in Q.S As-Saffat:102. This study uses the theory of family communication patterns with descriptive research methods. The findings of this study found that there are ethical aspects of Islamic communication carried out by the prophet Ibrahim and the prophet Ismail, and the pattern of communication carried out is authoritative. Keywords: Communication Pattern, Parent, Children, Quran Abstract Komunikasi dalam keluarga menjadi faktor penting dalam menentukan baik-buruknya sikap anak. Orangtua berperan penting dalam mendidik anak-anaknya. Dalam al-quran terdapat ban-yak komunikasi orangtua dan anak, salah satunya komunikasi antara nabiIbrahim dengan anaknya nabi Ismail. Kisah nabi Ibrahim dan nabi Ismail menjadi contoh yang baik bagi orangtua dan anak untuk dapat berkomunikasi secara baik dengan tetap mengutamakan aspek ketaatan kepada Allah SWT. Hal ini tertuang dalam Q.S As-Saffat ayat 102. Penelitian ini menggunakan teori pola komunikasi keluarga dengan metode penelitian deskriptif. Temuan penelitian ini ditemukan bahwa terdapat aspek etika komunikasi islam yang dilakukan nabi Ibrahim dan nabi Ismail, dan pola komunikasi yang dilakukan bersifat authoritaive. Kata Kunci: Pola Komunikasi, Orangtua, Anak, Al-quran